Amānat al-ʻIlm - Ahmaddin Ahmad Tohar (Al-Zahra : Journal for Islamic and Arabic Studies, 2007)
Science is a trustee. 'Trustee' must be the principle for the teachers, professors, researchers, and the prosecution of science in the search process, development, and deployment. It is important that science can be developed and exploited within the framework of the values of divinity and humanity. This paper describes science as a responsibility.